Black salve treatment of skin cancer: a review. (19th May 2018) - Lim, Alvin
Abstract: The use of complementary and alternative medicines in Australia has grown significantly. Much of this growth is due to their ease of accessibility from online vendors, often marketed with claims that are not scientifically tested. Black salve is a topical escharotic compound containing the active component sanguinarine, derived from the bloodroot plant. It has been advertised as a natural treatment for skin cancer. This article reviews the current state of black salve as an alternative skin cancer treatment, discussing its distribution and regulation, and provides a summary of clinical and laboratory studies. Clinical trials in this area are lacking, with most clinical data in the form of case reports demonstrating suboptimal therapeutic and cosmetic outcomes associated with its use. However, in vitro studies of sanguinarine suggest it causes indiscriminate destruction of healthy and cancerous tissue at doses higher than 5 µM, limiting its practical utility. It is vital that members of the public are aware of the potential effects and toxicity of commercial salve products.